Poles Apart: Monosporic, Bisporic, and Tetrasporic Embryo Sacs Revisited - Haig, David (Frontiers in Ecology and Evolution, 2020)
Bisporic embryo sacs contain nuclei derived from two members of a megaspore tetrad whereas tetrasporic embryo sacs contain nuclei derived from all four members of a tetrad. Megaspores from the same tetrad are less genetically similar than are megaspores from different tetrads. Therefore, cells derived from different megaspores in bisporic and tetrasporic embryo sacs are expected to compete with each other rather than cooperate. The tacit assumption of the plant embryological literature that bisporic and tetrasporic embryo sacs function as integrated organisms is demonstrably false, both theoretically and empirically. This competition within embryo sacs can be expressed as the formation of eggs by descendants of more than one megaspore or by the suppression of the descendants of all but one megaspore. Both phenomena have evolved multiple times. In contrast, all nuclei of monosporic female gametophytes are genetically identical. Consequently, monosporic development is predicted to be more evolutionarily stable than bisporic or tetrasporic development. The triploid endosperm produced by most monosporic gametophytes was probably derived from an ancestrally diploid endosperm and has been considered a key adaptation of the most successful lineages of flowering plants. The greater weight given to the doubled maternal genome in triploid endosperm may have facilitated a more efficient distribution of resources among a mother’s seeds because it reduced the influence of competition for maternal resources among unrelated paternal genomes of endosperm.